The secretome of stem cells isolated from the adipose tissue and wharton jelly acts differently on central nervous system derived cell populations - Ribeiro, Carlos A. (2012)
Introduction: It is hypothesized that administration of stromal/stem cells isolated from the adipose tissue (ASCs) and umbilical cord (HUCPVCs) can ameliorate the inured CNS. However it is still not clear whether they have similar or opposite effects on primary cultures of neuronal populations. The objective of the present work was to determine if ASCs and HUCPVCs preferentially act, or not, on specific cell populations within the CNS. Methods: Primary cultures of hippocampal neurons were exposed to ASCs and HUCPVCs conditioned media (CM) (obtained 24, 48, 72 and 96 hours after 3 days of culture) for 1 week. Results: Cell viability experiments (MTS test) revealed that CM obtained from both cell populations at all time points did not cause any deleterious effects on neuronal cells. In fact, it was determined that whenever the ASCs CM were supplemented with bFGF and B27, there was a significant increase on the metabolic viability and neuronal cell density of the cultures. On the other hand in the absence of CM supplementation, it was the HUCPVCs secretome that had the highest impact on the metabolic viability and cell density. In an attempt to unveil which factors could be involved in the observed effects, a screening for the presence of basic fibroblast growth factor (bFGF), nerve growth factor (NGF), stem cell factor (SCF), hepatocyte growth factors (HGF) and vascular endothelial growth factor (VEGF) in the CM was performed. Results revealed the presence of all these factors in ASCs CM, except bFGF; in contrast, in HUCPVCs CM it was only possible to detect robust NGF expression. Conclusions: Overall the results herein confirm important differences on the secretome of ASCs and HUCPVCs, which leads to distinct effects on the metabolic viability and neuronal cell densities in primary cultures of hippocampal neurons; however, the factor(s) that promote the stronger effect of the HUCPVCs CM in neuronal survival is (are) still to be identified.